The KDM Inhibitor GSKJ4 Triggers CREB Downregulation via a Protein Kinase A and Proteasome-Dependent Mechanism in Human Acute Myeloid Leukemia Cells - Illiano, Michela; Conte, Mariarosaria; Salzillo, Alessia; Ragone, Angela; Spina, Annamaria; Nebbioso, Angela; Altucci, Lucia; Sapio, Luigi; Naviglio, Silvio (Frontiers in Oncology, 2020)
Acute myeloid leukemia (AML) is a progressive hematopoietic-derived cancer arising from stepwise genetic mutations of the myeloid lineage. CREB is a nuclear transcription factor, which plays a key-role in the multistep process of leukemogenesis, thus emerging as an attractive potential drug target for AML treatment. Since epigenetic dysregulations, such as DNA methylation, histone modifications as well as chromatin remodelling, are a frequent occurrence in AML, an increasing and selective number of epi-drugs are emerging as encouraging therapeutic agents. Here, we demonstrate that the histone lysine demethylases (KDM) JMJD3/UTX inhibitor GSKJ4 results in both proliferation decrease and CREB protein down-regulation in AML cells. We found that GSKJ4 clearly decreases CREB protein, but not CREB mRNA levels. By cycloheximide assay we provide evidence that GSKJ4 reduces CREB protein stability; moreover, proteasome inhibition largely counteracts the GSKJ4-induced CREB down-regulation. Very interestingly, a rapid CREB phosphorylation at the Ser133 residue precedes CREB protein decrease in response to GSKJ4 treatment. In addition, PKA inhibition, but not ERK1/2 inhibition, almost completely prevents both GSKJ4-induced p-Ser133-CREB phosphorylation and CREB protein down-regulation. Overall, our study enforces the evidence regarding CREB as a potential druggable target, identifies the small epigenetic molecule GSKJ4 as an "inhibitor" of CREB, and encourages the design of future GSKJ4-based studies for the development of innovative approaches for AML therapy.